Challenges in managing children with Autism Spectrum Disorder and COVID-19: A case report - Shaji George (Academy of Family Physicians of Malaysia, 2021)
Children of all ages can be affected by coronavirus disease 2019 (COVID-19), although they appear to be less affected than adults in both incidence and severity. Difficulties arise in children with co-morbid conditions such as Autism Spectrum Disorder (ASD) with regard to isolation or quarantine, investigation, and management. It can be a challenge to manage such children, be it in a national COVID center or hospital or a tertiary center. We report our experience and the challenges we faced managing two siblings with ASD and COVID-19.